CODA 〓 OF LOCAL EARTHQUAKES OBSERVED ON THE SOUTHEAST TIBETAN PLATEAU : COMPARISON WITH LUTZOW-HOLM BAY REGION, EAST ANTARCTICA - アカマツ, ジュンペイ; カク, ヒロユキ; カナオ, マサキ; AKAMATSU, Junpei; KAKU, Hiroyuki; KANAO, Masaki (National Institute of Polar Research, 1995)
P(論文) Coda 〓 of local earthquakes observed at Bomi, southeast Tibetan plateau was evaluated using a single scattering model and compared with that in the Lutzow-Holm Bay region, East Antarctica. The results obtained are : (1) 〓^<-1> for short lapse time (SLT) from 5 to 50s shows large dependence on frequency; (2) 〓^<-1> for SLT in the Tibetan plateau region is larger than that in the Lutzow-Holm Bay region; (3) 〓^<-1> for long lapse time from 80 to 160s in the Tibetan region is nearly the same as that in the Lutzow-Holm Bay region. Although there is a need for discussion of coda excitation modeling, all these features are consistent with the general relation between coda 〓 and regional tectonic activities. departmental bulletin paper